ATS and AMF System Design for Solar Cell, Genset, and PLN at 2200 Watt Household Load - Hasdari Helmi Rangkuti; Muhammad Abiyyu Fathin Siregar (Universitas Islam Sumatera Utara, 2023)
The electricity generated by the generator is not always continuous in its distribution, the discontinuity of the electrical energy disturbs consumer comfort. The control system for moving from one source to another requires ATS (Automatic Transfer Switch) and AMF (Automatic Main Failure). In designing this control system, it will be made with Arduino mega and connected to the rele module, Arduino will regulate the transfer from each source to the load.The rele module is connected to several sources, such as PLN, Solar Cell, Generator Starter and Genset. Solar Cell operating hours are set at 12 noon to 5 pm, if at that hour the battery voltage is below 12V then the system will operate PLN as a voltage source and if at that hour PLN experiences a blackout then the system will operate the Genset as a voltage source. operational using PLN, if there is a blackout outside 12 noon to 5 pm then the system will operate the Genset for the electricity source and if at that time the Genset experiences a starter failure then the system will considered as turn off . The clock reading uses the RTC programmed on the Arduino Mega.The system is considered off when the PLN source experiences a blackout, the 100Ah 12V solar cell battery voltage does not exceed 12 V and the generator starter on the 3000 Watt Motoyama Generator fails so that the Arduino system reads the blackout. Arduino Mega is required to be able to read currents and voltages that occur in the system through current sensors and voltage sensors and will display on the LCD how much voltage and current is when the system is running. The duration of the move from the PLN source to the Solar Cell is 1s and the Genset starter duration reaches 5-10 s. This ATS and AMF system can be made at a household load of 2200 Watt, 220V,10A.